Psychological factors and the incidence of temporomandibular disorders in early adolescence - Luciano José Pereira; Tatiana Pereira-Cenci; Stela Márcia Pereira; Altair Antoninha Del Bel Cury; Glaucia Maria Bovi Ambrosano; Antônio Carlos Pereira; Maria Beatriz Duarte Gavião (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The purpose of the present study was to evaluate the relationship between psychological variables and the clinical diagnosis of temporomandbular disorders (TMD) in 12-year-old adolescents. TMD pain was assessed by RDC/TMD examination (Research Diagnostic Criteria for Temporomandibular Disorders) (Axis I and II). Five-hundred and fifty-eight subjects (330 girls and 228 boys) were examined. Bivariate analyses were performed using the Chi-square test (χ2). The logistic regression models were adjusted estimating the Odds Ratios (OR), their 95% confidence intervals (CI), and significance levels. Only 2.19% of the boys and 8.18% of the girls presented one of the Axis I categories. All variables from axis II were related to TMD diagnosis (p < 0.001). Gender was significantly related to TMD diagnosis (p = 0.0028). The risk of TMD incidence for girls was 3.5 times higher than that for boys (Odds Ratio = 3.52, Confidence Interval 1.31-9.43). The individuals who presented the variable "characteristics of pain intensity" (CPI) higher than 0 had 31 times more risk of TMD incidence (Odds Ratio = 31.361, Confidence interval 6.01-163.5). We concluded that psychological variables and female gender are important risk indicators related to TMD incidence, even in adolescents.